Estrabón e Iberia: la construcción de una identidad histórica - Cruz-Andreotti, Gonzalo (My University, 2014)
Strabo’s Iberia is a space under construction. Diverging process in the south, in the center, in the north, limiting very precisely territories finally converge in a new reality that is starting now: the roman-ization. Tipically, this long-span historical and geographical approach was adopted by the Greek historical geography, and propelled by geographers during the Principate of Augustus.
Strabo and Iberia: the construction of a historical identity
Keywords: Península Ibérica - Geografía antigua; España - Historia - <0218-0414 (Época romana); Estrabón; Península ibérica en la antigüedad; Augusto; Identidad; Etnogénesis; Romanización